Examining writing errors among Saudi EFL learners: Practices and perspectives - Ishtiaq, Muhammad; Hussain Shahid, Shahid; Muhammad Ishtiaq, Raja; Mohd Nasim, Saleem (LPMPP Universitas Negeri Yogyakarta, 2025)
Mastering error-free writing is challenging, especially for Arab EFL learners who often manifest these errors in areas such as grammar and mechanics. A step toward addressing these challenges is to explore the typical errors they encounter in writing. This study aims to examine Saudi EFL undergraduates’ writing difficulties using a sequential explanatory research design (a mixed-methods approach). In the quantitative phase, paragraphs written by 41 students were analyzed, and errors were identified and categorized. The qualitative phase involved semi-structured interviews with 23 participants to gain further insights into the types and causes of their writing errors and suggestions for improvement. The qualitative data were analyzed using ATLAS.ti 9. The results revealed that the most common errors identified were punctuation, capitalization, and grammar. However, participants’ views on spelling errors differed from their actual writing practices. They cited teaching methods, textbooks, and a lack of interest as reasons for their poor writing proficiency. Additionally, they believed that increased writing practice and the development of reading habits could improve their writing skills. These findings offer valuable insights for English language educators and learners, with implications for contextualized instruction, teaching practices, learning strategies, material development, and curriculum design.